2016
DOI: 10.15190/d.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dynamics of VE-cadherin at endothelial cell junctions at a glance: basic requirements and current concepts

Abstract: Intercellular junctions of the vascular endothelium are dynamic structures that display a high degree of plasticity, which is required to contribute to their regulation of many physiological and pathological processes including monolayer integrity, barrier function, wound healing and angiogenesis. Vascular endothelial cadherin (VE-cadherin) is connected via catenins to the actin cytoskeleton, both of which are key structures in endothelial junction regulation, and thus are the focus of much investigation. Fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…The local permeability studies showed that permeated regions were most affected by the number of punctate and no junction regions of coverage, which had a positive correlation with PR area. This result supports the generally accepted idea that continuous junctions are indicative of a more mature and stable barrier [60][61][62]. This study also implicates punctate (versus perpendicular) junctions in the regulation of monolayer permeability, though future investigation is needed to unveil the differences between these two discontinuous junction types.…”
Section: Discussionsupporting
confidence: 87%
“…The local permeability studies showed that permeated regions were most affected by the number of punctate and no junction regions of coverage, which had a positive correlation with PR area. This result supports the generally accepted idea that continuous junctions are indicative of a more mature and stable barrier [60][61][62]. This study also implicates punctate (versus perpendicular) junctions in the regulation of monolayer permeability, though future investigation is needed to unveil the differences between these two discontinuous junction types.…”
Section: Discussionsupporting
confidence: 87%
“…The mechanisms underlying cell junction remodeling involve actin-and myosinmediated contractility, tyrosine phosphorylation of VE-cadherin, p120 ctn -mediated endocytosis and the formation of actin-driven plasma membrane protrusions (Doggett and Breslin, 2011; Hoelzle and Svitkina, 2012;Martinelli et al, 2013;Adderley et al, 2015). In addition, live-cell imaging is being increasingly used (Day and Davidson, 2009;Frigault et al, 2009;Cranfill et al, 2016;Seebach et al, 2016;Hofer et al, 2018), as it allows the direct observations of junction remodeling with high spatial and temporal resolution, thus providing valuable hints regarding the underlying mechanisms. In this context, our laboratory has focused on the interdependency between actin-driven membrane protrusions and VE-cadherin-mediated adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The first problem relates to genetic manipulation of the endothelium, as these cells are hard to transfect by classical protocols. The use of viral vectors such as adenovirus and lentivirus vectors, however, has significantly increased the transfection rate and has been proven for sufficient application [for review, compare 11, 12]. Furthermore, if the dynamics of a protein interaction with different proteins is to be carried out, then in many cases different tags have to be cloned to the same protein.…”
Section: Introductionmentioning
confidence: 99%